The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.14453/aabfj.v14i3.3
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Initiatives and Disclosures by Large companies: The Views of Investors

Abstract: The purpose of this paper is to explore investors' perspectives on the environmental initiatives and disclosure strategies of large firms. Obtaining such viewpoints is important because, as signaling theory suggests that investors' perspectives are one of the contributory factors in determining organisational strategies for environmental initiatives and disclosures. We used a web-based questionnaire of a group of investors. We put forward a hypothetical case study that raised financial versus environmental con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Large cap firms are more transparent regarding environmental disclosure and as a result they are valued higher compared to small cap firms (Brammer & Pavelin, 2008;Siddique & Sciulli, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Large cap firms are more transparent regarding environmental disclosure and as a result they are valued higher compared to small cap firms (Brammer & Pavelin, 2008;Siddique & Sciulli, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Large cap firms are more transparent regarding environmental disclosure and as a result they are valued higher compared to small cap firms (Brammer & Pavelin, 2008; Siddique & Sciulli, 2020). Incorporation of environmental management in a firm's operation leads to increased perceived valuation of the firm (Klassen & McLaughlin, 1996).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study of Sen et al (2011) indicated that the quantity of environment data and the figures of Indian core industries differed across industries and companies, and that the information presented in annual reports was more descriptive than numerical. A large number of environmental reporting studies were conducted by Chatterjee and Zaman Mir (2008), Tilt (2001), Siddique (2015), Plumlee et al (2015), C. Deegan and Rankin (1996), Majumder et al (2019), and Anwar et al (2020), the outcomes of which mainly concentrated on the frequency and types of disclosure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ethical issues that impact the environment of the bank's business practices. Corporate responsibility towards the environment provides added value for all parties because the environment plays an important role not only for organizations but also for companies (Dosinta & Brata, 2020) and investors (Siddique & Sciulli, 2020). Collective actions of institutional investors will increase corporate accountability related to short-term financial aspects and environmental activities, society, climate change, and disclosure practices in corporate reporting (Rupley, Brown, & Marshall, 2012).…”
Section: Institutional Theory Sustainability Of the Company And Commu...mentioning
confidence: 99%